Analysis of operational harmonization of water allocation in a public irrigation system in Indonesia - a case study of Baro Raya irrigation area - Helmi HELMI; Hiroyuki TAKEYA (Acta Agriculturae Slovenica)
This study focused on operational procedure of water allocation across a public irrigation system in Indonesia. The objective is at achieving goals of water distribution in the attempt to gain both equity and efficiency. Methodology of this study is conducted through a series observation on the field that have implemented Pasten, Faktor-K, Faktor Palawija Relative (FPR) and Golongan methods as the step of water allocation procedures. Results of the study showed that these methods were carried out harmonically amongst the irrigated area according to the characteristic of its land and availability of water. There are no overlapping or varying of the methods using in each block. However, it was found some violations of operational rules due to lack of irrigation inspectors, malfunction of measurement structure, miss in assessing areas by crop type and planting date, and many tertiary blocks across more than one village.